On the assessment of the development of the digital educational environment of the Belarusian State University - Toustsik, Alena Ya. (University Pedagogical Journal, 2026)
A system for assessing the maturity of the digital educational environment at the Belarusian State University is presented. Such assessment is an important task on the path to implementing a sustainable and regulated educational process in the context of increasing uncertainty in modern education, provoked by the rapid introduction of technological innovations into education. Based on this framework, an analysis of the digital educational environment at the Belarusian State University was conducted.
Keywords: digitalisation of higher education; digital educational environment; framework of criteria for assessing the educational environment; DigCompOrg; Republican Information and Educational Environment